Does Mechanism of Injury Predict Trauma Center Need for Children?. (2nd January 2021) - Lerner, E. Brooke; Badawy, Mohamed; Cushman, Jeremy T.; Drendel, Amy L.; Fumo, Nicole; Jones, Courtney M. C.; Shah, Manish N.; Gourlay, David M.
Abstract: Objective: To determine if the Mechanism of Injury Criteria of the Field Triage Decision Scheme (FTDS) are accurate for identifying children who need the resources of a trauma center. Methods: EMS providers transporting any injured child ≤15 years, regardless of severity, to a pediatric trauma center in 3 midsized communities over 3 years were interviewed. Data collected through the interview included EMS observed physiologic condition, suspected anatomic injuries, and mechanism. Patients were then followed to determine if they needed the resources of a trauma center by reviewing their medical record after hospital discharge. Patients were considered to need a trauma center if they received an intervention included in a previously published consensus definition. Data were analyzed with descriptive statistics including positive likelihood ratios (+LR) and 95% confidence intervals (95%CI). Results: 9, 483 provider interviews were conducted and linked to hospital outcome data. Of those, 230 (2.4%) met the consensus definition for needing a trauma center. 1, 572 enrolled patients were excluded from further analysis because they met the Physiologic or Anatomic Criteria of the FTDS. Of the remaining 7, 911 cases, 62 met the consensus definition for needing a trauma center (TC). Taken as a whole, the Mechanism of Injury Criteria of the FTDS identified 14 of the remaining 62 children who needed the resources of a trauma center for a 77% under-triage rate. The mechanisms sustained were 36% fall (16 needed TC), 28% motor vehicle crash (MVC) (20 needed TC), 7% struck by a vehicle (10 needed TC), <1% motorcycle crash (none needed TC), and 29% had a mechanism not included in the FTDS (16 needed TC). Of those who sustained a mechanisms not listed in the FTDS, the most common mechanisms were sport related injuries not including falls (24% of 2, 283 cases with a mechanism not included) and assault (13%). Among those who fell from a height greater than 10 feet, 4 needed a TC (+LR 5.9; 95%CI 2.8-12.6). Among those in a MVC, 41 were reported to have been ejected and none needed a TC, while 31 had reported meeting the intrusion criteria and 0 needed a TC. There were 32 reported as having a death in the same vehicle, and 2 needed a TC (+LR 7.42; 95%CI: 1.90-29.0). Conclusion: Over a quarter of the children who needed the resources of a trauma center were not identified using the Physiologic or Anatomic Criteria of the Field Triage Decision Scheme. The Mechanism of Injury Criteria did not apply to over a quarter of the mechanisms experienced by children transported by EMS for injury. Use of the Mechanism Criteria did not greatly enhance identification of children who need a trauma center. More work is needed to improve the tool used to assist EMS providers in the identification of children who need the resources of a trauma center.